Comparative evaluation of four traction scenarios on a labially impacted dilacerated maxillary central incisor: a three-dimensional finite element analysis - Enas Senan Alyafrusee; Bowen Zheng; Wael Telha; Mengyao Li; Haopeng Wu; Xiaofeng Yang; Bushra Sufyan Almaqrami; Naseem Ali Al-Worafi; Majedh Abdo Ali Al-Somairi; Maged S. Alhammadi; Yi Liu (BMC Oral Health)
Abstract Objective This study aimed to analyze the stress distribution in the dentoalveolar structures of a labially impacted dilacerated maxillary central incisor during orthodontic traction, considering different positions of the traction button on the tooth’s crown through finite element analysis (FEA). Materials and methods Four three-dimensional (3D)finite element models (FEM) were created to simulate the maxilla of a 9-year-old female patient, featuring a left labially impacted dilacerated maxillary central incisor with the only variation being the position of the orthodontic traction button: at the incisal third of the labial surface (Model A), at the incisal third of the palatal surface (Model B), at the middle third of the palatal surface (Model C), and the cervical third of the palatal surface (Model D). Material parameters, grids, boundary conditions, coordinate systems, and load conditions were set in Ansys to establish the FEM for traction of the impacted incisor. A 100 g total traction force was applied between the button and a 0.016 × 0.022-inch stainless steel archwire in the direction perpendicular to the impacted tooth’s crown. The initial tooth displacements, biomechanical stress at the root apex, alveolar bone von Mises stress, and hydrostatic stress of the periodontal ligament (PDL) under the four conditions were analyzed and compared. Results The impact of traction button positioning on tooth displacement, stress distribution, and bone loading was assessed in four models. Model B demonstrated the highest labiopalatal and vertical displacement. The stress concentrations in the impacted tooth’s root were highest in model B, particularly in the cervical region labially, while model D showed the lowest root stress. Maximum stress in the alveolar bone was also observed in models A and B, particularly on the palatal surface near the cervical region. Hydrostatic stress in the periodontal ligament was highest in model B and lowest in model D. Conclusion The traction button positioned on the incisal third of the labial or palatal surface facilitates significant tooth movement. Still, it carries a higher risk of periodontal ligament damage, root and alveolar bone resorption. In contrast, the traction button positioned on the cervical third of the palatal surface, while less effective for movement, generates the least stress.